Keunikan Pembangunan Hotel Butik - Mohd Pauzei, Norsuhaila; Shamsudin, Zarina (Research in Management of Technology and Business, 2020)
The trend of hotel in Malaysia today has grown rapidly in line with the increase in tourism of the country. The increase in hotel industry in Malaysia has led to a variety of alternatives to overcome competition among them. The boutique hotel is the latest alternative in the hotel industry. This kind of hospitality is built with a good design or idea to create a unique and unique atmosphere for visitors. This new trend of hospitality has raised issues and concerns to the owners or managers of boutique hotels and visitors. The lack of information disclosure and data collection on the features of a boutique hotel as well as factors that attract visitors to this trend is consider as the weakness of the hotel boutique industry. Therefore, the objective of this study is to identify the characteristics of a boutique hotel and to study the factors that attract visitors to stay in a boutique hotel. This study will focus on boutique hotels in the Johor Bahru area. The primary data is gathered from observation, interviews involving 3 boutique hotel owners or managers and a questionnaire involving The results of this study have given the understanding and the collection of information about boutique hotels as well as visitor attractions on the atmosphere or environment, design, concept, location, service and boutique hotel facilities.